Antiviral activity of sulfated polysaccharides from marine algae and its application in combating COVID-19: Mini review. (February 2021) - Hans, Nidhi; Malik, Anushree; Naik, Satyanarayan
Abstract: Marine-derived sulfated polysaccharides possess various antiviral activities against a broad range of enveloped and non-enveloped viruses. It has become the potential source of antiviral drugs for pharmaceutical development. In this review, we will discuss the different types of sulfated polysaccharides and their structural classification. Some of the major sulfated polysaccharides with potent antiviral activity, including carrageenan, agar, ulvan, fucoidan, and alginates, are considered in this review. The mechanism of these sulfated polysaccharides in inhibiting the different stages of the viral infection process inside the host cell is also demonstrated. It involves blocking the initial entry of the virus or inhibiting its transcription and translation by modulating the immune response of the host cell. In addition, we explore the potential of sulfated polysaccharides as antiviral agents in preventing recent Corona Virus Disease-2019 (COVID-19). Graphical abstract: Unlabelled Image Highlights: Marine sulfated polysaccharides are a potential source of antiviral agents. Sulfated polysaccharides cover highly diverse structures. Inhibit the binding of the virus into the host cells Combat Coronavirus disease (COVID-19) pandemic Key research challenges and clinical trial are remaining.